2019
DOI: 10.1140/epjb/e2019-90514-3
|View full text |Cite
|
Sign up to set email alerts
|

Weyl systems: anomalous transport normally explained

Abstract: The chiral kinetic theory is derived from exact spinor mean field equations without symmetrybreaking terms for large classes of SU(2) systems with spin-orbit coupling. The influence of the Wigner function's off-diagonal elements is worked out. The decoupling of the diagonal elements renormalizes the drift according to Berry connection which is found as an expression of the meanfield, spin-orbit coupling and magnetic field. As special limit, Weyl systems are considered. The anomalous term ∼ EB in the balance of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 114 publications
(193 reference statements)
0
9
0
Order By: Relevance
“…From the asymmetry of F µν it follows that ∂ µ (j µ + i µ ) = 0, i.e., the current j µ + i µ is conserved. This is analogous to what happens with the chiral anomaly in Weyl systems, where the anomalous term can be rewritten as a current that satisfies the classical balance equation [13,14].…”
Section: Introductionmentioning
confidence: 83%
“…From the asymmetry of F µν it follows that ∂ µ (j µ + i µ ) = 0, i.e., the current j µ + i µ is conserved. This is analogous to what happens with the chiral anomaly in Weyl systems, where the anomalous term can be rewritten as a current that satisfies the classical balance equation [13,14].…”
Section: Introductionmentioning
confidence: 83%
“…and experimentally interpreted [ 11,15,16 ] as having observed a chiral anomaly. This has led to an enormous theoretical activity [ 17–19 ] describing, for example, anomalous transport, [ 20–25 ] the relation of chiral anomaly, and quantized Hall effects [ 26,27 ] up to chiral heat effect. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[44] it has been shown that a proper subtraction scheme of the infrared divergences shows that corresponding extra terms do not appear. Actually, the Lorentz‐invariant chiral kinetic theory can be derived from the quantum kinetic approach [ 25,45–50 ] leading to the chiral anomaly by many‐body correlations. A hint that the anomalies can be possibly explained by many‐body effects is also the relation of 2D conformal anomalies and virial expansions [ 51 ] and that the Dirac sea [ 52,53 ] can describe the Schwinger anomaly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations